RNA m6A reader IMP2/IGF2BP2 promotes pancreatic β-cell proliferation and insulin secretion by enhancing PDX1 expression - Laura Regué; Liping Zhao; Fei Ji; Hua Wang; Joseph Avruch; Ning Dai (Elsevier, 2021)
Background: Type 2 diabetes (T2D) is a common metabolic disease. Variants in human IGF2 mRNA binding protein 2 (IMP2/IGF2BP2) are associated with increased risk of T2D. IMP2 contributes to T2D susceptibility primarily through effects on insulin secretion. However, the underlying mechanism is not known. Methods: To understand the role of IMP2 in insulin secretion and T2D pathophysiology, we generated Imp2 pancreatic β-cell specific knockout mice (βIMP2KO) by recombining the Imp2flox allele with Cre recombinase driven by the rat insulin 2 promoter. We further characterized metabolic phenotypes of βIMP2KO mice and assessed their β-cell functions. Results: The deletion of IMP2 in pancreatic β-cells leads to reduced compensatory β-cell proliferation and function. Mechanically, IMP2 directly binds to Pdx1 mRNA and stimulates its translation in an m6A dependent manner. Moreover, IMP2 orchestrates IGF2-AKT-GSK3β-PDX1 signaling to stable PDX1 polypeptides. In human EndoC-βH1 cells, the over-expression of IMP2 is capable to enhance cell proliferation, PDX1 protein level and insulin secretion. Conclusion: Our work therefore reveals IMP2 as a critical regulator of pancreatic β-cell proliferation and function; highlights the importance of posttranscriptional gene expression in T2D pathology.